PELAKSANANAN REHABILITASI TERHADAP PECANDU NARKOBA SECARA SUKARELA DAN MELALUI PROSES PENEGAKAAN HUKUM. (STUDI KASUS DI BBNP JATENG) - Petrus Soerjowinoto; Tri Mulyo Wibowo; Simon Hermawan Baskoro (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
Indonesia is in a state of drug emergency, the prevalence of drug abuse is increasing, the growth of drug abuse users is already alarming and alarming. Ignorance of the dangers and risks of drug use will add to the victims of drug abuse. Efforts to solve drug problems are carried out in cross-sectoral aspects of preventive and repressive aspects. Based on the mandate of the regulation of drug addicts must undergo rehabilitation. Rehabilitation is an alternative sanction in the form of actions stipulated in a joint regulation. There are two ways that rehabilitation of drug abuse can be done voluntarily and through law enforcement processes and there is no involvement in the distribution of drugs. This paper will discuss about (1) the implementation of rehabilitation for drug addicts voluntarily (2) the implementation of rehabilitation for drug addicts through the process of law enforcement.